A second look at America - Aguinaldo, Emilio (Robert Speller & Sons, 1957)
This book is at once history and news. It is history because the man who fought a three-year war against the United States makes known for the first time his views on Philippine-American relations from 1898 to the present time. It is also news because, with originality and logic, he interprets present-day American world leadership in terms of its beginnings in the Philippines.